Comparison of the Effectiveness of Pre-urodynamic Single-dose Levofloxacin with Post-urodynamic Levofloxacin for Three Days Related to the Incidence of Urinary Tract Infection: A Randomized Control Trial - Rahardjo, Harrina Erlianti; Widia, Fina; Manurung, Mega Anara; Wicaksono, Indra; Soedarman, Soefiannagoya; Purwanto, Haryo Prakoso Adhi; Rizaly, Ahmad Aulia; Leonardo, Kevin; Afriansyah, Andika (Urology Journal, 2023)
Purpose: The current study aims to compare the effectiveness of pre-urodynamic single-dose levofloxacin and post-urodynamic levofloxacin for three days related to the incidence of urinary tract infections post-urodynamic examination. Materials and Methods: This is a single-blind randomized clinical trial conducted in three outpatient urology centers in Jakarta: Cipto Mangunkusumo General Hospital, Siloam Asri Hospital, and Persahabatan General Hospital using a consecutive sampling method between July 2019 - February 2022. The outcome of the study is the incidence of urinary tract infections in both treatment groups. Urinary tract infection was defined as a patient with one or more clinical symptoms of lower urinary tract infection and one or more urinalysis parameters positive for urinary tract infections. Chi-square was used to evaluate the association where p < 0.05 was used to determine statistical significance. Results: A total of 126 patients (63 patients in each arm) were included in the evaluation and analysis. Overall, urinary tract infections were detected in 25 cases (19.8%), 12 patients from the pre-urodynamic antibiotic group (9.5%) and 13 patients from the post-urodynamic antibiotic group (10.3%) (P = .823). E.coli was the most common bacteria found in the urine culture. Conclusion:There is no significant difference between a single dose of 500 mg of Levofloxacin administered one hour before the urodynamic study and a once-daily dose of 500 mg of Levofloxacin for three days following the urodynamic study related to urinary tract infections prevention post-urodynamic examination.